2016
DOI: 10.5937/ffr1601019t
|View full text |Cite
|
Sign up to set email alerts
|

Influence of growth conditions on biofilm formation of Listeria monocytogenes

Abstract: Listeria monocytogenes is ubiquitous in nature and a major concern for the food industry, since it is the causal agent of the serious foodborne illness listeriosis. This organism can be introduced through many routes to food-processing environments and may become established on food-processing equipment. Subsequently, food products may become contaminated during processing. In addition, the bacterium can grow at refrigeration temperatures. Biofilms are regarded as important with respect to the survival and gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…On the other hand, Zeraik and Nitschke 14 demonstrated that L. monocytogenes produced more biofilm in nutrient rich medium. In the present study, BHI broth was used because it has been reported as an effective medium to promote biofilm formation by L. monocytogenes isolates from different origins, at various surfaces 2, 15. It was observed 10 6 –10 8 CFU of L. monocytogenes /cm 2 were present in biofilms formed on stainless steel and glass coupons, despite incubation times evaluated.…”
Section: Discussionmentioning
confidence: 86%
“…On the other hand, Zeraik and Nitschke 14 demonstrated that L. monocytogenes produced more biofilm in nutrient rich medium. In the present study, BHI broth was used because it has been reported as an effective medium to promote biofilm formation by L. monocytogenes isolates from different origins, at various surfaces 2, 15. It was observed 10 6 –10 8 CFU of L. monocytogenes /cm 2 were present in biofilms formed on stainless steel and glass coupons, despite incubation times evaluated.…”
Section: Discussionmentioning
confidence: 86%
“…; Tomičić et al . ), all performed in microtiter plates and at temperatures ranging between 7 and 42°C, nutrient‐rich medium was reported to favour increased L. monocytogenes biofilm formation. However, in a few of these studies (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…Due to its ability to produce biofilm, L. monocytogenes is more resistant to antibiotics, host immune system [7,8], biocides, or stress [13,14]. L. monocytogenes can produce biofilms on various surfaces used in medicine or industry, such as polystyrene, glass, and stainless steel [15,16].…”
Section: Discussionmentioning
confidence: 99%